The Comparison Between Ad Valorem and Unit Taxes under Monopolistic Competition - Philipp J. H. Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper shows that the welfare dominance of ad valorem over unit taxes under imperfect competition, extends to the Dixit-Stiglitz framework with differentiated products, entry and love of variety. This contrasts against findings by Anderson et al. (J Public Econ, 2001) made in a similar framework, but under Bertrand competition.
Keywords: D43; L13; H22; H21; 330; Unit tax; Specific tax; Ad valorem tax; Welfare; Umsatzsteuer; Verbrauchsteuer; Monopolistischer Wettbewerb; Wohlfahrtseffekt; Theorie